Anterior thoracic depression with paradoxical breathing: About a case treated by substernal traction - Soto Cordano, José; Gilardoni, Federico; Estrugo, Roberto (Cirugía del Uruguay, 1978)
The paper refers to a case of anterior Thoracic fracture with externo-costal decollement and paradoxical breathing. This is an extremely serious condition and the author reviews its anatomicaI variations complications and Muses of death, with emphasis on the importance and priority assigned in treatment in case of pneumothorax, above all other procedures. Advantages derived from the simple procedure of substernum traction in this variety of costal flap are remarkes.